Konsep Diyat dalam Diskursus Fiqh - Aksamawanti Aksamawanti (Syariati: Jurnal Studi Al-Qur'an dan Hukum, 2016)
This article aims to provide an overview of the concept of blood-money paymentsin fiqh. Wi is a treasure that must be paid and provided by the offender to the victim or his guardian jinayah damages, caused jinayah made by the offender tokorban yang done. Wi assigned to someone because, first, intentional homicide offenders were pardoned by the family were killed. second, manslaughter; third, asimilar murder intentional; ketiga, crime on other people. Blood-money paymentform can be a camel, gold, silver, based on some of the provisions of hadith. The objective of the diyat is a human survival in the world, preventive measures sothat people do not kill each other which would result in chaos in society, terhadap protection of victims, and to uphold justice in society.